2004
DOI: 10.1128/mcb.24.8.3140-3149.2004
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of LANP/pp32 Null Mice

Abstract: The leucine-rich acidic nuclear protein (LANP) belongs to a family of evolutionarily conserved proteins that are characterized by an amino-terminal domain rich in leucine residues followed by a carboxy-terminal acidic tail. LANP has been implicated in the regulation of a variety of cellular processes including RNA transport, transcription, apoptosis, vesicular trafficking, and intracellular signaling. Abundantly expressed in the developing cerebellum, this protein has also been hypothesized to play a role in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
33
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 43 publications
4
33
1
Order By: Relevance
“…Recently, the generation of pp32/PHAPI-deficient mice has been reported, and extensive analyses of their general and neuronal development failed to detect any abnormalities. 36 While apoptosis regulation has not been specifically addressed in this study, the knockdown of pp32/PHAPI in HeLa cells by RNAi technology has also been reported as inconclusive. 20 These negative reports were explained by possible overlapping functions of the multiple forms of PHAP proteins, some of which have probably arisen by gene duplication.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, the generation of pp32/PHAPI-deficient mice has been reported, and extensive analyses of their general and neuronal development failed to detect any abnormalities. 36 While apoptosis regulation has not been specifically addressed in this study, the knockdown of pp32/PHAPI in HeLa cells by RNAi technology has also been reported as inconclusive. 20 These negative reports were explained by possible overlapping functions of the multiple forms of PHAP proteins, some of which have probably arisen by gene duplication.…”
Section: Discussionmentioning
confidence: 80%
“…The expression of ANP32A in brain tissues also indicates that this molecule may play a neurologic role in OA. Its expression in the cerebellum could indicate a role in the coordination of movements, for instance, or in proprioception (30).…”
Section: Discussionmentioning
confidence: 99%
“…34 However, a recent study showed that pp32-null mice have no apparent phenotypes for the most part compared with their wild-type littermates. 35 This may be due to the compensatory role of pp32 closely related family members, which continue to be expressed in pp32-deficient mice. Mice lacking two or more pp32 family members need to be generated to test their functions of pp32 and related family members in development and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%